Deglaciation of the Eurasian ice sheet complex - Patton, Henry; Hubbard, Alun Lloyd; Andreassen, Karin; Auriac, Amandine; Whitehouse, Pippa L.; Stroeven, Arjen P.; Shackleton, Calvin; Winsborrow, Monica; Heyman, Jakob; Hall, Adrian M. (Quaternary Science Reviews, 2017)
The Eurasian ice sheet complex (EISC) was the third largest ice mass during the Last Glacial Maximum with a span of over 4500 km and responsible for around 20 m of eustatic sea-level lowering. Whilst recent terrestrial and marine empirical insights have improved understanding of the chronology, pattern and rates of retreat of this vast ice sheet, a concerted attempt to model the deglaciation of the EISC honouring these new constraints is conspicuously lacking. Here, we apply a first-order, thermomechanical ice sheet model, validated against a diverse suite of empirical data, to investigate the retreat of the EISC after 23 ka BP, directly extending the work of Patton et al. (2016) who modelled the build-up to its maximum extent. Retreat of the ice sheet complex was highly asynchronous, reflecting contrasting regional sensitivities to climate forcing, oceanic influence, and internal dynamics. Most rapid retreat was experienced across the Barents Sea sector after 17.8 ka BP when this marine-based ice sheet disintegrated at a rate of ∼670 gigatonnes per year (Gt a −1 ) through enhanced calving and interior dynamic thinning, driven by oceanic/atmospheric warming and exacerbated by eustatic sea-level rise. From 14.9 to 12.9 ka BP the EISC lost on average 750 Gt a −1 , peaking at rates >3000 Gt a −1 , roughly equally partitioned between surface melt and dynamic losses, and potentially contributing up to 2.5 m to global sea-level rise during Meltwater Pulse 1A. Independent glacio-isostatic modelling constrained by an extensive inventory of relative sea-level change corroborates our ice sheet loading history of the Barents Sea sector. Subglacial conditions were predominately temperate during deglaciation, with over 6000 subglacial lakes predicted along with an extensive subglacial drainage network. Moreover, the maximum EISC and its isostatic footprint had a profound impact on the proglacial hydrological network, forming the Fleuve Manche mega-catchment which had an area of ∼2.5 × 10 6 km2 and drained the present day ...